2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7590822
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based driver fatigue detection using hybrid deep generic model

Abstract: Abstract-Classification of electroencephalography (EEG)-based application is one of the important process for biomedical engineering. Driver fatigue is a major case of traffic accidents worldwide and considered as a significant problem in recent decades. In this paper, a hybrid deep generic model (DGM)-based support vector machine is proposed for accurate detection of driver fatigue. Traditionally, a probabilistic DGM with deep architecture is quite good at learning invariant features, but it is not always opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…But the classification running time was not reported in this study. In [38], Deep Generic Model (DGM)-SVM was utilized to classify EEG data. Their best classification accuracy was 73.29%.…”
Section: Final Classificationmentioning
confidence: 99%
“…But the classification running time was not reported in this study. In [38], Deep Generic Model (DGM)-SVM was utilized to classify EEG data. Their best classification accuracy was 73.29%.…”
Section: Final Classificationmentioning
confidence: 99%
“…The deep belief network (DBN) based DDD system obtained 91.10 % of sensitivity and 55.48 % of specificity. The same approach was also utilized in [29] by using the CNN model on EEG signals. The authors reported that deep-learning methods achieved better accuracy compare to traditional machinelearning algorithms [21][22][23][24].…”
Section: Related Workmentioning
confidence: 99%
“…San et al [35] used a deep generic model (DGM) and support vector machine to detect driver fatigue. They compared the performance of power spectrum density features-based SVM and deep generic modelbased SVM and found that DGM-based SVM performed better in terms of sensitivity, specifity and accuracy.…”
Section: Dong and Wumentioning
confidence: 99%